2018
DOI: 10.2478/jeb-2018-0013
|View full text |Cite
|
Sign up to set email alerts
|

Political and Economic Institutions and Economic Performance: Evidence from Kosovo

Abstract: This study examines Kosovo’s attempts to create efficient political and economic institutions while assuming that if these institutions cannot perform well and the market economy will also fail. Thus, the main aim of this paper is to understand the reasons behind institutional and economic failure. A qualitative research approach that we used is based on a longitudinal perspective and a set of secondary data which are analyzed by using Qualitative Content Analysis technique. Our findings suggest that the state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 62 publications
0
23
0
Order By: Relevance
“…/ COVID-19 impact and firm reactions towards crisis: Evidence from a transition economy to decreased incomes and low performance. It is important to emphasize that SMEs in Kosovo faced constant growth challenges even during the pandemic situation (Krasniqi, 2007) due to the failed attempt of the government to ensure a stable institutional and business environment (Kryeziu & Coşkun, 2018). The pandemic situation has worsened the situation of SMEs and firms from all industries.…”
Section: Financial Determinants Of Sme Activity In Developing Countriesmentioning
confidence: 99%
See 1 more Smart Citation
“…/ COVID-19 impact and firm reactions towards crisis: Evidence from a transition economy to decreased incomes and low performance. It is important to emphasize that SMEs in Kosovo faced constant growth challenges even during the pandemic situation (Krasniqi, 2007) due to the failed attempt of the government to ensure a stable institutional and business environment (Kryeziu & Coşkun, 2018). The pandemic situation has worsened the situation of SMEs and firms from all industries.…”
Section: Financial Determinants Of Sme Activity In Developing Countriesmentioning
confidence: 99%
“…These findings are not in line with Shen et al (2020) and Chowdhury et al (2020), who suggest that COVID-19 influenced particular industries that were more vulnerable to the pandemic situation. The possible explanation on why all industries in the case of Kosovo have been negatively influenced is that industries are not as developed due to the lack of technological capabilities and focus on becoming more competitive in international markets, due to uncertainty in the business environment and a lack of consistent pro-market reforms (Kryeziu & Coşkun, 2018;Krasniqi, 2007).…”
Section: Financial Determinants Of Sme Activity In Developing Countriesmentioning
confidence: 99%
“…The study context is a transition economy of Kosovo characterised by deficient formal institutional settings, uncertain business environment and firm internationalisation which is challenging (Kryeziu and Coskun, 2018;Kadriu et al, 2019). Firms in Kosovo face several institutional and non-institutional barriers including the financial, institutional, human and managerial capacities that hamper their growth in the long term (Krasniqi, 2007(Krasniqi, , 2010Dana and Ramadani, 2015).…”
Section: Rq2mentioning
confidence: 99%
“…As pointed out by Schillo, Persaud and Jin (2016) and others (Raza, Muffatto, and Saeed 2019;Ács, Autio, and Szerb 2014), however, relatively few studies have effectively examined the specific institutional factors that impact entrepreneurial activity and intent on a national scale. More recently publications show that scholars are interested on factors impacting entrepreneurial activity at a national level (Pfiefer et al 2021;Kryeziu and Coşkun 2018) and across countries (Sugiyanto and Yolanda 2020;Siljak 2018). These and other authors have suggested that such factors tend to modulate the rate of entrepreneurship at the national level (Ács et al 2012;Audretsch and Keilbach 2008).…”
Section: Background Literature Reviewmentioning
confidence: 99%